2021
DOI: 10.1109/tvcg.2020.3003823
|View full text |Cite
|
Sign up to set email alerts
|

PRS-Net: Planar Reflective Symmetry Detection Net for 3D Models

Abstract: In geometry processing, symmetry is a universal type of high-level structural information of 3D models and benefits many geometry processing tasks including shape segmentation, alignment, matching, and completion. Thus it is an important problem to analyze various symmetry forms of 3D shapes. Planar reflective symmetry is the most fundamental one. Traditional methods based on spatial sampling can be time-consuming and may not be able to identify all the symmetry planes. In this paper, we present a novel learni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 53 publications
(77 reference statements)
0
59
0
1
Order By: Relevance
“…Our improvements in performance may have been small due to noisy estimates of symmetry features. Recent advances in geometry processing using classical methods as well as deep learning have led to better symmetry detectors both on 3D models of objects [25], [29], [31] and 2D objects embedded in natural scenes [26], [30]. Further, there have been efforts to reduce the sample complexity of deep neural networks by designing convolutional filters that capture various symmetries in the training data [27], [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our improvements in performance may have been small due to noisy estimates of symmetry features. Recent advances in geometry processing using classical methods as well as deep learning have led to better symmetry detectors both on 3D models of objects [25], [29], [31] and 2D objects embedded in natural scenes [26], [30]. Further, there have been efforts to reduce the sample complexity of deep neural networks by designing convolutional filters that capture various symmetries in the training data [27], [28].…”
Section: Discussionmentioning
confidence: 99%
“…Symmetry is an important property in our perception [9], [10], [23] that we detect far better than machine algorithms [24]. Symmetry detection in an image is a challenging problem that has been studied extensively [24], [25], [26] including more recently using neural networks [27], [28], [29], [30], [31]. Recent studies have suggested a role for local ribbon symmetry in contours in scene categorization [32].…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission from Ref. [120]. we discuss 3D shape applications based on different 3D representations, including shape analysis and shape reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Symmetry is important in 3D shapes, and can be further used in many other applications such as shape alignment, registration, completion, etc. Gao et al [120] designed the first unsupervised deep learning method, PRS-Net (planar reflective symmetry net), to detect planar reflective symmetry in 3D shapes, using a new symmetry distance loss and a regularization loss, as illustrated in Fig. 6.…”
Section: Symmetry Detectionmentioning
confidence: 99%
“…For computation of the symmetry using machine learning approaches, Gao et al developed a convolutional neural network (CNN) to estimate the plane of symmetry of a set of objects including tables, cabinets and boats [10]. The CNN required training data to input into the model.…”
Section: Introductionmentioning
confidence: 99%